Diet of nectarivorous bats from the National Park Cerros de Amotape, Tumbes - Arias, Edith (2009)
In Peru 18 species of nectarivorous bats are reported, however little information about their diet is available. This study is the first report about pollen consumption of the nectar-feeding bat species Glossophaga soricina, Lonchophylla hesperia, and Anoura geoffroyi in the dry forest and the Pacific Tropical rainforest of the National Park Cerros de Amotape, Tumbes. We analyzed 21 stomach contents and identified eigth pollen morphotypes belonging to the families Bombacaceae, Cactaceae, Fabaceae, Solanaceae, Rubiaceae, Myrtaceae, Malvaceae, and Rosaceae; and found floral evidences of the chiropterophilous syndrome in Bombacaceae, Cactaceae, Fabaceae, Solanaceae, and Rubiaceae. We found that A. geoffroyi consumed pollen of Ceiba trichistandra, Solanaceae, and Rubiaceae; G soricina consumed of Abutilon reflexum, Armathocereus cartwrightianus, C. trichistandra, and Rubiaceae; and L. hesperia of A. cartwrightianus, Eriobotrya japonica, Fabaceae, and Psidium sp.; suggesting that these bat species have a generalist diet. The bats G. soricina and A. geoffroyi shared the consumption of the ceiba C. trichistandra and the Rubiaceae, while G. soricina and L. hesperia shared the consumption of the cactus A. cartwrightianus. The other five morphotypes were not shared. In addition, we found that the ceiba C. trichistandra was the species most consumed by bats, specially G. soricina.